2012
DOI: 10.1016/j.foodqual.2011.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Effects of noise and distraction on alcohol perception

Abstract: a b s t r a c tRecent research demonstrated that noise unconnected to the target stimulus can alter taste perception of food, but it is not clear whether similar effects might be seen with respect to alcohol. This is particularly important, as it might help explain previous reports of higher/faster alcohol consumption in loud music environments. In the between subjects experiment here, participants (n = 80) completed standardised taste and olfactory tests, followed by a taste test of alcoholic beverages varyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
72
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(77 citation statements)
references
References 26 publications
5
72
0
Order By: Relevance
“…and the higher level semantic judgments that people make about a wine's qualities (see [23][24][25][26][27][28][29][30][31][32][33][34][36][37][38][39][40][41][43][44][45][46][47][48][49][50][51]). It would therefore be interesting in future research, to compare people's rating of a wine when the putatively matching music is played versus when mismatching music is played instead.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…and the higher level semantic judgments that people make about a wine's qualities (see [23][24][25][26][27][28][29][30][31][32][33][34][36][37][38][39][40][41][43][44][45][46][47][48][49][50][51]). It would therefore be interesting in future research, to compare people's rating of a wine when the putatively matching music is played versus when mismatching music is played instead.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, several other studies have now demonstrated that changing the music that happens to be playing in the background affects people's rating of everything from whisky ( [26]; see also [27]) through to a bittersweet chocolate dessert [28], and from gelato [29] through to functional and dietetic foods [30], not to mention beer [31][32][33]. What we hear, then, can exert a profound influence on what we taste -and no less importantly on what we think we taste (see [34], for a review).…”
Section: Château Climens Sauternes 2001mentioning
confidence: 99%
“…This too might be expected to influence our perception and appreciation of wine [22,23]. A growing body of scientific evidence also demonstrates that sounds that are too loud can lead to a crossmodal suppression of taste and alcohol perception (e.g., [24][25][26]; see [27] for a review). Finally here, one could imagine how even simply knowing that a particular piece of music had been chosen, or better still, composed, to go with a specific wine could exert a generalized uplift effect on one's multisensory tasting experience (cf.…”
Section: Modifying the Tasting Experience With Musicmentioning
confidence: 99%
“…In another recent study, Stafford et al [20] had 80 participants take a sip from each of five alcoholic drinks (varying in alcohol strength). These researchers reported that auditory stimulation (that is, music that had been pre-selected to be distracting), affected participants' ability to discriminate the relative alcohol content of the various drinks.…”
Section: On the Unisensory Manipulation Of The Atmospherementioning
confidence: 99%